2019
DOI: 10.1186/s12909-019-1623-x
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning in antimicrobial stewardship: innovation in medical education

Abstract: Background This study aimed to analyse the impact that web-based distance learning has on knowledge gain in medical students, as well as student perceptions of the methodology. Methods This was an educational intervention study conducted at a tertiary teaching hospital in the city of São Paulo, Brazil. From 2008 to 2014, we offered a free web-based distance learning course, covering antimicrobial use and microbial resistance, to fifth-year medical students. The course e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
(14 reference statements)
0
12
0
1
Order By: Relevance
“…As far as time organization is concerned, curricula studies have shown that early introduction of AMR teaching as well as repetitive and enriched training upon antibiotic resistance, diagnosis, management, prescribing and communication skills would lead to a more comprehensive understanding of the challenges and complexities of infectious diseases [ 43 , 46 , 47 , 48 ]. Moreover, e-learning and online education about AMS is a desirable and effective method according to medical professionals and students [ 41 , 49 ], although a European survey questions the successfulness of this means [ 35 , 50 ]. Furthermore, a study based on a seminar for medical students included real patients and their advocates.…”
Section: Discussionmentioning
confidence: 99%
“…As far as time organization is concerned, curricula studies have shown that early introduction of AMR teaching as well as repetitive and enriched training upon antibiotic resistance, diagnosis, management, prescribing and communication skills would lead to a more comprehensive understanding of the challenges and complexities of infectious diseases [ 43 , 46 , 47 , 48 ]. Moreover, e-learning and online education about AMS is a desirable and effective method according to medical professionals and students [ 41 , 49 ], although a European survey questions the successfulness of this means [ 35 , 50 ]. Furthermore, a study based on a seminar for medical students included real patients and their advocates.…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that only 40% of students were aware of the term 'antimicrobial stewardship' and only a few of them felt ready for the practice of prescribing antibiotics (5). After the completion of an online course, 93.6% of medical students believed that the medical curriculum involved topics about the appropriate use of antibiotics and antimicrobial stewardship (12). Usually, the majority of educational interventions occur during postgraduate while behaviors and attitudes toward prescribing started to form and developed (13).…”
Section: Discussionmentioning
confidence: 99%
“…The modules included both theoretical information as well as virtual patients. Significant improvement in mean knowledge scores was observed between pre and post intervention assessments (5.78 vs 8.45, p < 0.001) [ 15 ]. Similarly, Heath et al reported an improvement in AMS knowledge among 103 nurses at long-term care facilities after completing online learning modules.…”
Section: Main Textmentioning
confidence: 99%